Effect of applied voltage and temperature on methane production and microbial community in microbial electrochemical anaerobic digestion systems treating swine manure. (1st July 2019) - Yu, Jaecheul; Kim, Sunwon; Kwon, O-Seob
Abstract: Microbial electrochemical technology (MET) that can harvest electricity/valuable materials and enhance the efficiency of conventional biological processes through the redox reaction of organic/inorganic compounds has attracted considerable attention. MET-based anaerobic digestion (AD) systems treating swine manure were operated at different applied voltages (0.1, 0.3, 0.5, 0.7, and 0.9 V) and temperatures (25, 35, and 45 °C). Among the MET-based AD systems with different applied voltages at 35 °C, M4 at 0.7 V showed the highest methane production (2.96 m 3 -CH4 /m 3 ) and methane yield (0.64 m 3 -CH4 /kg-VS). The methane production and yield increased with increasing temperature at an applied voltage of 0.7 V. Nevertheless, the MET-based AD systems (LM at 25 °C and 0.7V) showed competitive AD performance (2.33 m 3 -CH4 /m 3 and 0.53 m 3 -CH4 /VS) compared with the conventional AD system (35 °C). The microbial community was affected by the applied voltage and temperature, and hydrogenotrophic methanogens such as M. flavescens, M. hungatei, and M. thermautotrophicus were mainly responsible for methane production in MET-based AD systems. Therefore, the methane production can be enhanced by an applied voltage or by direct interspecies electron transfer because M. flavescens and M. thermautotrophicus were especially predominant in cathode of MET-based AD systems. The MET-based AD systems can help enhance biogas production from swine manure with no significant change in methane content. Furthermore, MET-based AD systems will be a promising AD system through low material development and the optimal operation.